(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Pathomorphosis of epilepsy is a process of evolutionclinical (neurophysiological, epidemiological) picture of the disease under the influence of various factors or their combination related to the internal and external environments of the body. Pathomorphosis can be natural and induced, positively and negatively directed. Positive pathomorphosis is characterized by a tendency towards the development of protective and compensatory mechanisms of the body that help smooth out or reduce the manifestations of the disease; with a negative pathomorphosis, the opposite picture is observed.